Long-term passive acoustic recordings track the changing distribution of North Atlantic right whales (Eubalaena glacialis) from 2004 to 2014. Issue 1 (December 2017) - Davis, Genevieve; Baumgartner, Mark; Bonnell, Julianne; Bell, Joel; Berchok, Catherine; Bort Thornton, Jacqueline; Brault, Solange; Buchanan, Gary; Charif, Russell; Cholewiak, Danielle; Clark, Christopher; Corkeron, Peter; et al.
Abstract Given new distribution patterns of the endangered North Atlantic right whale (NARW;Eubalaena glacialis ) population in recent years, an improved understanding of spatio-temporal movements are imperative for the conservation of this species. While so far visual data have provided most information on NARW movements, passive acoustic monitoring (PAM) was used in this study in order to better capture year-round NARW presence. This project used PAM data from 2004 to 2014 collected by 19 organizations throughout the western North Atlantic Ocean. Overall, data from 324 recorders (35, 600 days) were processed and analyzed using a classification and detection system. Results highlight almost year-round habitat use of the western North Atlantic Ocean, with a decrease in detections in waters off Cape Hatteras, North Carolina in summer and fall. Data collected post 2010 showed an increased NARW presence in the mid-Atlantic region and a simultaneous decrease in the northern Gulf of Maine. In addition, NARWs were widely distributed across most regions throughout winter months. This study demonstrates that a large-scale analysis of PAM data provides significant value to understanding and tracking shifts in large whale movements over long time scales.